Initiation of continental accretion in the betique rif domain - (:unkn) unknown (My University, 2019)
The thermo-chronological study of syn- to post-rift and syn-orogenic sediments makes it possible to reconstruct the time-temperature evolution of the basins at the different stages of the orogenesis. This study combined with structural and stratigraphic observations makes it possible to determine the spatial and temporal evolution of the passive margin from the early stages of its inversion to the final stages of the collision associated with the rapid exhumation of the metamorphic internal units. The Betic and Rif cordilleras belong to the western end of the peri-Mediterranean chains. The geodynamic history associated with the formation of the Betics since the Oligocene is deeply marked by a combination of processes of slab retreat, tearing and delamination of the continental and / or oceanic lithosphere in the context of convergence between Africa and Europe. In response, the crust that today forms the Alboran Basin and the internal areas of Betic and Rif has been subject to extension in the back arc area since the Oligocene. This extension phase was synchronous with the compressive deformations recorded in the Meso-Cenozoic coverage of the Iberian and North African margins and the formation of the pleated pre-country chains. The use of fission and (U-Th) / He low-temperature thermochronological analyzes on apatite applied to the Cretaceous and Tertiary flysch series of the Mauretanian and Massylian domains highlights the importance of a phase of Paleogene exhumation. Combined with structural and stratigraphic observations, it appears that this episode of exhumation is associated with the development of a foreland all along the Betic Cordillera for nearly 400 km. An examination of structural relationships between flyschs, subbetic series and the Triassic shows that salt tectonics played a major role. This observation leads to explain the current structure of the external zones of the Betics while decreasing the extent of the tectonic movements. Combi
Keywords: African Research